Pengaruh Persepsi dan Motivasi Mahasiswa Akuntansi Terhadap Minat Mengikuti MBKM Dengan Personalitas Sebagai Variabel Moderating - Sadiyah, Chalimatu; Sudaryanti, Dwiyani; Maslichah, Maslichah (e_Jurnal Ilmiah Riset Akuntansi, 2024)
This study aims to determine the effect of perceptions and motivation of accounting students on interest in participating in "MBKM" with personality as a moderating variable. The data collection technique in this study was carried out through distributing questionnaires. The data analysis method used is Moderated Regression Analysis with descriptive statistical testing, data quality test (validity and reliability test), normality test, classical assumption test (multicollinearity test and heteroscedasticity test), and hypothesis testing (simultaneous F test, determination coefficient test, and t test). The results of this study indicate that the perception and personality of accounting students have a positive effect on the interest in joining "MBKM". In contrast, the motivation of accounting students has no effect on the interest in joining "MBKM". In addition, personality cannot moderate the effect of perception and motivation of accounting students on interest in joining "MBKM".Keywords: Perception, motivation, student interest on MBKM, and personality